Does Artificial Intelligence Based Green Supply Chain Improve Sustainable Economic Performance? Evidence from Indonesian Firms - Oktavianna, Rakhmawati; Mononym, Benarda; Atmaja , Sri Nitta Crissiana Wirya; Rizal , Anis Syamsu (International Review of Management and Marketing, 2026)
This study examines the role of artificial intelligence adoption in optimizing Green Supply Chains and how its practices can improve Sustainable Economic Efficiency in the Indonesian manufacturing sector. A survey was conducted among manufacturing companies that have integrated AI into their green supply chains. The study employed SEM processed using AMOS, resulting in the finding that AI adoption significantly improves GSC practices, which in turn significantly contributes to sustainable economic efficiency. Furthermore, the results confirm that GSC acts as a mediating between artificial intelligence and Sustainable Economic Efficiency. This study highlights the strategic importance of incorporating innovative AI use in sustainable practices, offering practical insights for managers to align AI applications with green objectives. For policymakers, these findings underscore the potential of AI-powered GSC as a catalyst for national sustainability and decarbonization efforts, emphasizing the need for standardized sustainability policies, incentives, and metrics to create sustainable economic efficiency in Indonesia.